Radio Link Quality Estimation in Low-Power Wireless Networks - Baccour, Nouha. (SpringerBriefs in Electrical and Computer Engineering, 2013)
This book provides a comprehensive survey on related work for radio link quality estimation, which covers the characteristics of low-power links, the fundamental concepts of link quality estimation in wireless sensor networks, a taxonomy of existing link quality estimators and their performance analysis. It then shows how link quality estimation can be used for designing protocols and mechanisms such as routing and hand-off. The final part is dedicated to radio interference estimation, generation and mitigation.